Cardiotrophin‐1 contributes to metabolic adaptations through the regulation of lipid metabolism and to the fasting‐induced fatty acid mobilization. Issue 12 (13th October 2020) - Carneros, David; Medina‐Gómez, Gema; Giralt, Marta; León‐Camacho, Manuel; Campbell, Mark; Moreno‐Aliaga, Maria J.; Villarroya, Francesc; Bustos, Matilde
Abstract: It is becoming clear that several human pathologies are caused by altered metabolic adaptations. During liver development, there are physiological changes, from the predominant utilization of glucose (fetal life) to the use of lipids (postnatal life). Fasting is another physiological stress that elicits well‐known metabolic adjustments. We have reported the metabolic properties of cardiotrophin‐1 (CT‐1), a member of the interleukin‐6 family of cytokines. Here, we aimed at analyzing the role of CT‐1 in response to these metabolic changes. We used different in vivo models. Furthermore, a differential study was carried out with wild‐type and CT‐1 null mice in fed (ad libitum) and food‐restricted conditions. We demonstrated that Ct‐1 is a metabolic gene induced in the liver via PPARα in response to lipids in mice (neonates‐ and food‐restricted adults). We found that Ct‐1 mRNA expression in white adipose tissue directly involved PPARα and PPARγ. Finally, the physiological role of CT‐1 in fasting is confirmed by the impaired food restriction‐induced adipose tissue lipid mobilization in CT‐1 null mice. Our findings support a previously unrecognized physiological role of CT‐1 in metabolic adaptations, through the regulation of lipid metabolism and contributes to fasting‐induced free fatty acid mobilization.